Differential temperature control in heat-integrated pressure-swing distillation for separating azeotropes to deal with operating pressure fluctuations. (September 2020) - He, Yongchao; Li, Ye; Zheng, Kaitian; Li, Guoning; Guo, Zheng; Xu, Chunjian
Highlights: First time implementing systematic assessment of DTC in HI-PSD. Verified the robustness of DTC in HI-PSD. The comparison between DTC and PCTC showed that their dynamic controllabilities are almost the same. Valuable inspiration for the control of other heat-integrated distillation processes. Abstract: For heat-integrated pressure-swing distillation (PSD) in which the heat release of overhead vapor condensation of high-pressure column (HPC) is completely utilized to supply the reboiler duty of low-pressure column (LPC), the operating pressure (OP) of the HPC cannot be controlled. Pressure-compensated temperature control (PCTC) is widely used to hold the controlled temperature under OP fluctuations to achieve effective control. In this paper, differential temperature control (DTC) is applied to control the sensitive-stage temperature under OP fluctuations of the HPC in the control of a variety of heat-integrated PSD processes, including both conventional and entrainer-assisted PSD, both partially and fully heat-integrated PSD, both LPC->HPC and HPC->LPC sequence, and separating both minimum-boiling and maximum-boiling azeotropes. IAE of the product purities of all the processes are calculated. Systematic comparison between DTC and PCTC is implemented. The results show that effective control can be achieved when implementing DTC in these processes and the dynamic performances of DTC and PCTC are almost the same. Therefore, DTC can be applicable in the control of heat-integrated PSD for separating binary azeotropes, which is also a good inspiration for other heat-integrated distillation processes.